18F-FLT PET performs better than 18F-FDG PET in differentiating malignant uterine corpus tumors from benign leiomyoma - Yamane, Tomohiko; Takaoka, Aki; Kita, Masato; Imai, Yukihiro; Senda, Michio (Annals of nuclear medicine, 2012)
Purpose The aim of this study is to test the hypothesis that positron emission tomography (PET) with 3′-deoxy-3′-[ 18 F]-fluorothymidine ( 18 F-FLT) can differentiate malignancy from benign leiomyoma better than PET with 2-deoxy-2-[ 18 F]fluoro- d -glucose ( 18 F-FDG), and to evaluate whether 18 F-FLT and 18 F-FDG uptake correlate with immunohistochemical index of cell proliferation. Methods The protocol of this prospective study was approved by the institutional ethics committee, and all patients gave written informed consent. Fifteen patients (aged 26–65 years, median 44 years) with uterine corpus tumor which has the possibility of being leiomyosarcoma underwent 18 F-FLT and 18 F-FDG PET scans. Maximum standard uptake value (SUV max ) of PET scans and Ki-67 labeling index of surgical specimens were evaluated. Mann–Whitney’s U test was used for comparing uptakes between benign and malignant, and linear regression analysis was used for evaluating the correlation between Ki-67 labeling index and SUV max . Results Five cases were diagnosed as malignant (leiomyosarcoma for 3 cases, and carcinoma for 2 cases), and the others were benign leiomyoma. Sensitivity and negative predictive value of both tracers for detecting malignancy was 100 %. Specificity, positive predictive value and accuracy of 18 F-FLT PET were higher than those of 18 F-FDG PET. Difference in SUV max between malignant and benign was significant for 18 F-FLT PET ( P < 0.01), but not for 18 F-FDG PET. While all the malignant cases showed positive uptake in both tracers, a case of leiomyosarcoma with huge necrosis showed relatively low uptake. Uptake of 18 F-FLT showed better correlation with Ki-67 labeling index compared with 18 F-FDG ( R 2 = 0.91 vs. R 2 = 0.26). Conclusion Negative findings on additional 18 F-FDG or 18 F-FLT PET may rule out the possibility of malignancy for the patients with suspected leiomyosarcoma diagnosed by conventional methods. 18 F-FLT PET is superior to 18 F-FDG PET in differentiating malignant from benign leiomyoma. Moreover, 18 F-FLT uptake correlated well with the immunohistochemical index of cell proliferation.